1938
DOI: 10.1017/s0022172400011311
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of coliform organisms in milk and the accuracy of the presumptive coliform test

Abstract: 1. The presumptive coliform test was carried out by each of three workers, at each of four dilutions, on seventeen sets of five tubes for each of seven samples of 18-hour-old afternoon milk, held overnight in the ice chest.2. With the exception of three slightly anomalous results, the data are consistent with the hypothesis that the chance of a tube remaining sterile is constant for all tubes inoculated from the same sample of milk at any one dilution.3. The assumption of a Poisson distribution of organisms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1941
1941
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…and thought that part at least of the inaccuracy of the coliform test might be due to the structure of the ordinary Durham tube, which failed to ensure the collection of the gas produced. Barkworth & Irwin (1938) investigated the accuracy of the coliform test. Their results, in which each of three workers made seventeen tests on each of seven samples, each test consisting of five-fold inoculation at four different levels, showed that a wide variation might occur in the proportion of positive and negative tubes, though not at any one dilution in excess of that expected by chance.'…”
Section: Part I Description Of Experimentsmentioning
confidence: 99%
“…and thought that part at least of the inaccuracy of the coliform test might be due to the structure of the ordinary Durham tube, which failed to ensure the collection of the gas produced. Barkworth & Irwin (1938) investigated the accuracy of the coliform test. Their results, in which each of three workers made seventeen tests on each of seven samples, each test consisting of five-fold inoculation at four different levels, showed that a wide variation might occur in the proportion of positive and negative tubes, though not at any one dilution in excess of that expected by chance.'…”
Section: Part I Description Of Experimentsmentioning
confidence: 99%
“…It is frequently only practicable to determine the density (A) of microorganisms in solution by diluting the sample to such an extent that only a small proportion of subsamples displays positive growth (Barkworth and Irwin 1938;Dickson 1989;Best 1990;Blais and Yamazaki 1991;Turpin et al 1993). This technique is commonly referred to as the dilution method.…”
Section: Introductionmentioning
confidence: 99%
“…In this manuscript we elaborate a simple maximum probability resolution (SMPR) method which involves recurring calculations (j iterations) of Aj+] by the addition of a term, related to a,P, (Appendix), to Aj until the MPN (A, = ARnd) is reached. All other computer-based MPR methods (Best 1990;Briones and Reichardt 1999) with which we are familiar are more involved than our technique inasmuch as our SMPR algorithm involves only the addition of a simple summation to an arbitrary initial guess of the MPN. Other computerbased MPN methods (non-MPR) are equally straightforward to execute but cannot be used for lesser numbers of observations (n S 24) per dilution (Irwin et al 2000b; i.e., not accurate at low n).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is exceedingly ingenious, and ofremarkably high efficiency, but it cannot always be applied and the conditions for its applicability may sometimes be opposed to the best interests of experimental design. Halvorson & Ziegler (1933) suggested the use of the principle of maximum likelihood for estimating the density, and suggestions for the systematic computation of the maximum likelihood estimate have been made by Barkworth & Irwin (1938) and Finney (1947). Mather's (1949) solution to a closely related problem leads to an ideal method of computing the maximum likelihood estimate for a dilution series.…”
mentioning
confidence: 99%